2023
DOI: 10.1098/rspb.2023.1514
|View full text |Cite
|
Sign up to set email alerts
|

No link between handedness and spatial navigation: evidence from over 400 000 participants in 41 countries

P. Fernandez-Velasco,
A. Coutrot,
H. Oloye
et al.

Abstract: There is an active debate concerning the association of handedness and spatial ability. Past studies used small sample sizes. Determining the effect of handedness on spatial ability requires a large, cross-cultural sample of participants and a navigation task with real-world validity. Here, we overcome these challenges via the mobile app Sea Hero Quest. We analysed the navigation performance from 422 772 participants from 41 countries and found no reliable evidence for any difference in spatial ability between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…This explanation is supported by the mean score of 28.45 in the Montreal Cognitive Assessment in our population, above what would be expected for a population this age (26.3), see Borland et al (2017). Note that self-selection bias -not necessarily of physically active older participants, but rather of older participants with a higher-than-average cognitive function -might also affect the global sample of Sea Hero Quest players, where there is higher variability after the age of 60 (Coutrot et al, 2018; for an exploration of selection bias in this age group, see Fernandez-Velasco et al, 2023). Our results mirror those of Hill et al, (2024), who found older participants' decline in navigation ability was mitigated when the virtual world was presented in a more naturalistic medium (immersive VR) compared to when it was presented on a flat desk-top screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation is supported by the mean score of 28.45 in the Montreal Cognitive Assessment in our population, above what would be expected for a population this age (26.3), see Borland et al (2017). Note that self-selection bias -not necessarily of physically active older participants, but rather of older participants with a higher-than-average cognitive function -might also affect the global sample of Sea Hero Quest players, where there is higher variability after the age of 60 (Coutrot et al, 2018; for an exploration of selection bias in this age group, see Fernandez-Velasco et al, 2023). Our results mirror those of Hill et al, (2024), who found older participants' decline in navigation ability was mitigated when the virtual world was presented in a more naturalistic medium (immersive VR) compared to when it was presented on a flat desk-top screen.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al, 2023). Studies using Sea Hero Quest have found that gender inequality across countries (gender gap index) predicts gender differences in navigation ability (Coutrot et al, 2018), that 7 hours of sleep is associated with a better navigation performance late in life across cultures (Coutrot et al, 2022a;Yavuz et al, 2024a), or that neither handedness (Fernandez-Velasco et al, 2023) nor GPS reliance (Yavuz et al, 2024b) are associated with spatial ability, while education is (Coutrot et al 2023). Cultural norms around masculinity have been found associated with over-estimation of navigation performance across countries (Walkowiak et al 2023).…”
Section: Introductionmentioning
confidence: 99%